2018
DOI: 10.31436/iiumej.v19i2.886
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Need for Specific Propagation Model for Specific Environment Based on Different Terrain Characteristics

Abstract: Owing to their speed of excution as well as their limited reliance on detailed knowledge of the terrain characteristics of the service environments, empirical propagation models have enjoyed general acceptability in the wireless communication research community. However, recent industrial observations show that no single propagation model can best fit all the radio service environments, which led to the hypothesis of specific models for specific environments. In order to scientifically verify this hypothesis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
2
5
0
Order By: Relevance
“…This indicates that the path loss prediction potential of the developed path loss model for this study performs better than that of COST 231-Hata as its path loss prediction value is lower than that of COST 231-Hata. This result buttresses the finding in [8], which was verified scientifically in [9] that specific path loss model ought to be developed for specific location for better quality signal reception of broadcasting signal in each location.…”
Section: Comparative Performance Evaluation Of Developed Model With An Existing Modelsupporting
confidence: 85%
See 4 more Smart Citations
“…This indicates that the path loss prediction potential of the developed path loss model for this study performs better than that of COST 231-Hata as its path loss prediction value is lower than that of COST 231-Hata. This result buttresses the finding in [8], which was verified scientifically in [9] that specific path loss model ought to be developed for specific location for better quality signal reception of broadcasting signal in each location.…”
Section: Comparative Performance Evaluation Of Developed Model With An Existing Modelsupporting
confidence: 85%
“…5 revealed that the exponent of the predictions made by COST 231-Hata model is given mathematically as; The brief review of these three propagation models reveals that availability of correction factors are essential for direct application of model(s) developed in a particular terrain to be used in another terrain(s). The review also buttresses the findings in [8,9] that there is need for different empirical models for different types of radio signals at different locations under different conditions or terrains. Furthermore, the brief review buttresses the finding reported in [25] that a radio propagation model, which gives an acceptable prediction in one location might not be suitable in another location.…”
Section: Cost 231-hata Modelsupporting
confidence: 59%
See 3 more Smart Citations